Biomimetics: A Versatile Approach towards Multifunctional Robust Microcapsules with Tunable, Restorable, and Solvent‐Proof Superhydrophobicity for Self‐Healing and Self‐Cleaning Coatings (Adv. Funct. Mater. 43/2014). (November 2014) - Wu, Gang; An, Jinliang; Tang, Xiu‐Zhi; Xiang, Yong; Yang, Jinglei
<x xml:space="preserve">Abstract</x> Multifunctional superhydrophobic polymeric microcapsules with lotus‐leaf‐like hierarchical surface structure and moisture‐sensitive core are prepared by J. Yang and team on page 6751 by a facile and versatile strategy. The microcapsules exhibit superior shell tightness against solvents and heat, and possess widely tunable, repetitiously self‐restorable, and solvent‐proof superhydrophobicity. By incorporating these microcapsules in coating matrix, a biomimetic smart coating is developed, seamlessly combining self‐healing and self‐cleaning functionalities for anticorrosion and antifouling applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>